2012
DOI: 10.1007/s12325-011-0092-3
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Brimonidine/Timolol and Dorzolamide/Timolol on Ocular Perfusion Pressure and Blood Flow in Glaucoma

Abstract: Introduction: To examine the comparative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…By contrast to these findings Siesky et al [26] found that brinzolamide and dorzolamide may provide an increase in retinal oxygen saturation in patients with primary open angle glaucoma without any influence on the retrobulbar blood supply. In another published study Siesky et al [19] also compared the effects of dorzolamide/timolol and brimonidine/timolol combinations on ocular blood flow in a 1‐month period and found the same results with their previous study. Both studies included 15 primary open angle glaucoma patients.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…By contrast to these findings Siesky et al [26] found that brinzolamide and dorzolamide may provide an increase in retinal oxygen saturation in patients with primary open angle glaucoma without any influence on the retrobulbar blood supply. In another published study Siesky et al [19] also compared the effects of dorzolamide/timolol and brimonidine/timolol combinations on ocular blood flow in a 1‐month period and found the same results with their previous study. Both studies included 15 primary open angle glaucoma patients.…”
Section: Discussionsupporting
confidence: 62%
“…Since Harris et al [9] reported topical dorzolamide accelerated the blood velocity in the retinal and superficial optic nerve head but had no effect on retrobulbar hemodynamics, several studies have been conducted to achieve a clear and distinct result regarding the relationship between topical CAI and retrobulbar blood flow [3,9,16–21]. Although dorzolamide alone is not the most potent agent to lower IOP, compared with surgery or even with other topical antiglaucoma medications, it has a dual action, the vasodilating and IOP lowering effect.…”
Section: Discussionmentioning
confidence: 99%
“…After application of brimonidine, reduced blood flow in the choroid was observed by Weigert et al3 and in the ciliary body by Reitsamer et al1 These findings are in accordance with our findings. However, other authors found no significant effect on OBF, particularly at the back of the eye in glaucoma patients 2832…”
Section: Discussionmentioning
confidence: 88%
“…The pre-OCTA literature suggests that while IOP decreases in glaucoma patients treated with topical timolol, OBF does not increase 59 , 60 and often declines. 61 , 62 Many studies confirm, however, that treatment with timolol in combination with dorzolamide 63 , 64 or, as was more recently demonstrated, brimonidine 64 elevates OBF in addition to lowering IOP. In our study, in all cases but one, timolol treatment was provided in combination with dorzolamide and/or brimonidine, so we do not expect medication use to have caused reduced OBF.…”
Section: Discussionmentioning
confidence: 90%